PEMERANAN TEATER MELALUI DONGENG SEBAGAI MEDIA PENDIDIKAN KARAKTER DI PKBM OMAH DONGENG MARWAH - Wicakksana, Orion Bima; Makaf, Akhyar (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2024)
This study aims to analyze the application of theater acting through fairy tales as a medium for character education at PKBM Omah Dongeng Marwah.The research method used is qualitative. Primary data sources are interviews and observations of educators, learners, and related parties. Secondary data are obtained from literature studies. The research was conducted at PKBM Omah Dongeng Marwah, located at Jl. Ngasinan No. 9, Purworejo Village, Bae District, Kudus Regency. The research subjects were 15 people who were selected purposively according to research needs. The research instruments used included interview guides, observation sheets, and questionnaires. The research was conducted for three months from January to March 2024. This study also compared data from interviews, observations, and documents to ensure the validity and consistency of the data.The results of the study showed that this approach was effective in developing the character of learners, improving communication skills, creativity, and teamwork. The main conclusion is that this method can have a significant positive impact on the personal and professional development of learners.